Research Opportunities for Medications to Treat Alcohol Dependence: Addressing Stakeholders' Needs. (24th July 2013) - Litten, Raye Z.; Falk, Daniel; Ryan, Megan; Fertig, Joanne
<x xml:space="preserve">Abstract</x> During the past decade, significant advances have been made in the development of medications to treat alcohol dependence. Four medications have been approved by the U.S. Food and Drug Administration for treating alcohol dependence—naltrexone, injectable naltrexone, acamprosate, and disulfiram—and several others show promise. The fact remains, however, that because of the heterogeneity of alcohol dependence, these medications will not work for all people, in all circumstances. Moreover, clinicians are not routinely prescribing these medications for alcohol treatment. This commentary poses a number of issues that must be addressed in order to advance the alcohol research field and to make medications a mainstream treatment for problematic drinking. These issues are framed from the perspective of the various stakeholders involved, including clinicians, patients, regulatory agencies, the pharmaceutical industry, and third‐party payers. Addressing these issues will not only help to improve treatment but, as further described, will also open up many new research opportunities for alcohol investigators in the coming decade.